Evaluation of human risks of surface water and groundwater contaminated with Cd and Pb in the southern El-Minya Governorate, Egypt - S. A. Salman; A. A. Asmoay; A. El-Gohary; H. Sabet (Drinking Water Engineering and Science, 2019)
Water pollution with cadmium (Cd) and lead (Pb) is a worldwide concern because of their health impact. Determination of their concentrations and potential human health risks in surface water and groundwater in the southern El-Minya Governorate, Egypt, is the main aim of this study. Fifty-five samples were collected, 30 surface water samples and 25 groundwater samples. The samples were analyzed using atomic absorption spectrometry to determine Cd and Pb contents. Their levels in surface water and groundwater exceeded the maximum allowable level for drinking water set by the World Health Organization (WHO). The hazard quotient showed that the surface water and groundwater may pose a health risk to residents, especially to children.